Réponses

Meilleure réponse !
2013-03-15T12:59:16+01:00

1) 5x - (x + 3 ) = 3 ( x - 2 )

5x - ( x + 3 ) = 3x - 6

5x - x + 3 - 3x + 6 = 0

x + 9 = 0

x = - 9

 

2) - (-2x + 8) - 5x (3x + 4) = -5 ( 3x^2 - 2)

2x - 8 - 15x^2 - 20x = -15x^2 + 10

2x - 8 - 15x^2 - 20x + 15x^2 - 10 = 0

2x - 8 20x -10 = 0

-18x -18 = 0

x = 1

 

3) x/2 - 5 = -7/2 + 2x

x/2 - 5 + 7/2 - 2x = 0

x/2 - 4x/2 - 5 + 7/2 = 0

x - 4x /2 - 10/2 + 7/2 = 0

-3x/2 - 17/2 = 0

-3x - 17 = 0

x = -17/3

 

4) x^2 - 21 = 4

x^2 - 21 - 4 = 0

x^2 - 25 = 0

supposant x^2 = 2x

alrs on a : 2x = 25

x = 25/2

x = 12.5

 

5) ( 3x + 2 )^2 - 16 = 0

9x^2 + 12x + 4 - 16 = 0

9x^2 + 12x - 12 = 0

si x^2 = 2x alrs on a : 9*2x + 12x - 12 = 0

18x + 12x - 12 = 0

30x - 12 = 0

30x = 12

x = 2/5